2020
DOI: 10.21203/rs.2.12555/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with child health service delivery by female community health volunteers in Nepal: Findings from a national survey

Abstract: Background: Nepal has made a significant improvement in child survival in the last few decades and the involvement of female community health volunteers (FCHVs) has been crucial in such achievement. While there have been a lot of documented studies and reports, rarely has been explored the status and factors associated with the child health service provided by these volunteers. The aim of this study was to identify the factors associated with the child health service delivery by FCHVs.Methods : A national surv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Furthermore, as prior studies [10] , [14] , [15] stated, it was clear that the monthly meeting of FCHVs leads to improved knowledge of maternal health among village mothers. Also, it was identified that FCHVs used to visit the pregnant woman's home to inform them of ANC education and check their condition [20] . The statement adds weight to dispersing the debates in the literature, arguing lake of care during pregnancy or childbirth [26] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as prior studies [10] , [14] , [15] stated, it was clear that the monthly meeting of FCHVs leads to improved knowledge of maternal health among village mothers. Also, it was identified that FCHVs used to visit the pregnant woman's home to inform them of ANC education and check their condition [20] . The statement adds weight to dispersing the debates in the literature, arguing lake of care during pregnancy or childbirth [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, evidence showed that villagers have developed trust with FCHVs over time by their selfless volunteering of maternal services such as home visiting or door-to-door visits [19] . In addition, they notice the danger signs including the vaginal bleeding and heavy pain, severe headaches and trouble breathing in postpartum women and new-borns during postnatal home visits and they can advise the new mother how to take care of the baby [20] .…”
Section: Introductionmentioning
confidence: 99%